Induction and preliminary characterization of neoplastic pulmonary nodules in a transgenic pig model. (April 2023) - Ghosn, Mario; Elsakka, Ahmed S.; Petre, Elena N.; Cheleuitte-Nieves, Christopher; Tammela, Tuomas; Monette, Sebastien; Ziv, Etay; Schachtschneider, Kyle M.; Srimathveeravalli, Govind; Yarmohammadi, Hooman; Edward Boas, F.; Solomon, Stephen B.
Highlights: In transgenic pigs carrying KRASG12D and TP53R167H Cre-inducible mutations, AdCre percutaneous and endovascular inoculations induced neoplastic lung nodules in 2/6 and 1/10 attempts, respectively. All lung tumors were visible at the 1-week computed tomography, and appeared as well-circumscribed solid nodules, with a median longest diameter of 14 mm (range: 5–27 mm). Tumors consisted of inflammatory undifferentiated neoplasms composed of atypical spindle and epithelioid cells and/or a fibrovascular stroma and abundant mixed leukocytic infiltrate. Atypical cells diffusely displayed expression of vimentin and some showed expression of CK WSS and CK 8/18. Abstract: Objectives: Lung cancer models in large animals are lacking. Oncopigs are transgenic pigs that carry both KRAS G12D and TP53 R167H Cre-inducible mutations. This study aimed to develop and histologically characterize a swine model of lung cancer that could serve for preclinical studies evaluating locoregional therapies. Materials and Methods: In two Oncopigs, an adenoviral vector encoding the Cre-recombinase gene (AdCre) was injected endovascularly through the pulmonary arteries or inferior vena cava. In two other Oncopigs, a lung biopsy was performed and incubated with AdCre, before reinjecting the mixture into the lungs percutaneously. Animals were clinically and biologically (complete blood count, liver enzymes and lipasemia) monitored. Obtained tumors were characterized on computed tomography (CT) and on pathology and immunohistochemistry (IHC). Results: Neoplastic lung nodules developed following 1 (1/10, 10%) endovascular inoculation, and 2 (2/6, 33%) percutaneous inoculations. All lung tumors were visible at the 1-week CT, and appeared as well-circumscribed solid nodules, with a median longest diameter of 14 mm (range: 5–27 mm). Only one complication occurred: an extravasation of the mixture into the thoracic wall during a percutaneous injection that resulted in a thoracic wall tumor. Pigs remained clinically healthy during the entire follow-up (14–21 days). On histology, tumors consisted of inflammatory undifferentiated neoplasms composed of atypical spindle and epithelioid cells and/or a fibrovascular stroma and abundant mixed leukocytic infiltrate. On IHC, atypical cells diffusely displayed expression of vimentin and some showed expression of CK WSS and CK 8/18. The tumor microenvironment contained abundant IBA1 + macrophages and giant cells, CD3 + T cells, and CD31 + blood vessels. Conclusion: Tumors induced in the lungs of Oncopigs are fast growing poorly differentiated neoplasms associated with a marked inflammatory reaction that can be easily and safely induced at site specific locations. This large animal model might be suitable for interventional and surgical therapies of lung cancer.